Implementasi Strategi Cyber Public Relations Website www.tangandiatas.com Dalam Mengembangkan Informasi UMKM Melalui Komunitas - Alifiah Ghaniyyu Widyaningrum (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2022)
Website www.tangandiatas.com is one of the largest entrepreneurial communities in Indonesia, where Indonesian entrepreneurs join. As the largest community, one of the developments is to make a community of leading entrepreneurs who have a positive contribution to civilization and form entrepreneurs who are tough and successful in creating synergies among fellow members with the principle of high then community, the website www.tangandiatas.com was formed. In the realm of communication science, researchers see how the implementation of the cyber public relations strategy website www.tangandiatas.com in developing MSME information through the community? And what are the activities carried out by public relations in an effort to develop community MSMEs to take advantage of digital platforms?Broadly speaking, Public Relations strategy, both online and conventional, there is a process of Public Relations strategy. According to Cutlip and Center in (Danandjaja 2011) there are four processes of a dynamic Public Relations strategy, which means that every element is continuous with one another. The four processes are: Defining Problems, Planning and Programs, Action and Communication, Program Evaluation. This Cyber PR strategy uses the ROPE (Reasearch, Objectives, Programming, Evaluation) method or the RACE (Research, Action, Communication, Evaluation) formula.The approach used in this study is a qualitative approach, namely a research approach without using statistical figures but with descriptive exposure, namely trying to describe a symptom, event, event that is happening now, where the researcher tries to photograph events and events that occur to be the focus of his attention for later. described as is. The method used is descriptive qualitative research method, which is a research procedure that produces descriptive data in the form of written or spoken words from the people and actors observed, directed from the background of the individual as a whole (holistic) without isolating the individual and his organization in variables but view it as part of a whole. (Sugiyono 2008).The researcher describes the research results in the form of a narrative. Samples from the population taken through the sampling technique process are purposive sampling. The researcher took as a sample Opinion Leader, namely the founding board of TDA (Tangan Di Atas), Community Administrators, and members of the TDA community. Data collection techniques through in-depth interviews and environmental observation of the research sample. In data analysis the researcher tested the validity of the data through data triangulation, namely triangulating different data sources of information by examining the evidence that came from these sources and using it to build a coherent justification for themes (Moleong 2016). to compare the situation and perspective of the informant with various opinions and views, as well as compare the results of the interview with the contents of a document related to comparing opinions or circumstances between perspectives